Monoplant® the Indonesian Implant: The Overview of Implant and Its Development - Gunardi, Eka R. (Indonesian Socety of Obstetrics and Gynecology, 2011)
Norplant®, as a first-generation levonorgestrel implant and containing six capsules, has been shown to be effective as long-term contraception since more than 25 years ago. In the process, then the number of implants was reduced to two rods called Norplant-2®, which is then updated into Jadena® (in Indonesia) or Jadelle® (in America). As a country with the largest implant acceptors in the world, Indonesia has developed its own implant method consisting of two rods called Indoplant®. Currently being developed implant that consists of single rod called Monoplant®. Monoplant® is expected to be the best option because it only consists of a single rod implant that is easy to insertion and remove, effective and safe for at least three years. [Indones J Obstet Gynecol 2011; 35-1: 40-6]